Addressing survivorship care gaps through digital innovation: opportunities, challenges, and ethical considerations in the e-QuoL project - Demoor-Goldschmidt, Charlotte; Michel, Gisela; Roganovic, Jelena; Thierry-Chef, Isabelle; Lähteenmäki, Päivi M.; Muraca, Monica; Jakab, Zsuzsanna; Chevenez, Lola; Potter, Emma J.; Garami, Miklós; Thornton; Kristen; et al. (BioMed Central, 2026)
Background
Childhood, adolescent, and young adult cancers (CAYAC) present unique challenges in oncology. Advances in treatment Have led to an 80% 5-year survival rate; however, CAYAC survivors (CAYACS) remain at high risk of long-term medical and psychosocial complications, significantly impacting their quality of life. Short and long-term follow-up care is recommended, but is often fragmented, with considerable disparities in availability and accessibility across Europe. Many existing digital tools primarily address medical needs, leaving psychosocial challenges unaddressed. The e-QuoL project aims to bridge these gaps by leveraging existing digital health solutions to provide equitable, person-centered survivorship care.
Methods
The e-QuoL project employs a participatory approach involving survivors, families, healthcare professionals (HCP), and researchers. Using the FormIT methodology, the project follows three phases: Explore, Create, and Evaluate. The Explore phase includes a large-scale cross-sectional survey across 15 European countries to assess the unmet needs of CAYACS and their families. The Create phase involves co-creation workshops to develop and refine digital tools, including MyCaree-QuoL tool, which will supplement survivorship care passports, to provide personalized medical and psychosocial support. The Evaluate phase comprises usability testing and clinical studies in at least seven European countries to assess effectiveness, scalability, and real-world applicability.
Discussion
The e-QuoL project builds on existing digital health innovations while adapting them to diverse European healthcare systems. By developing MyCaree-QuoL, the project fosters a decentralized, person-centered model of survivorship care to promote equal access to quality survivorship support for CAYACS and HCPs. Ethical considerations, including data privacy, patient consent, and equitable access, are central to the project, with dedicated Ethics and Social Challenge Groups guiding implementation. Digital disparities remain a challenge, particularly for survivors from lower socio-economic backgrounds or remote areas. To mitigate this, e-QuoL will work with healthcare professionals to offer additional in-person support to complement digital interventions. The project aligns with Europe’s Beating Cancer Plan, aiming to improve quality of life and reduce disparities in care. By fostering collaboration among 30 partners across 15 countries and hosting resources on the PanCare website, e-QuoL seeks to ensure long-term impact, contributing to the goal of high-quality, equitable survivorship care across Europe.